The economic consequences of regulatory changes in employee stock options on corporate bond holders: SFAS No.123R and structural credit model perspectives - Chen, Tsung-Kang; Liao, Hsien-Hsing; Chi, Cheng-Ming (Journal of Banking & Finance, 2014)
Based upon structural credit models, we investigate the changes of the effects of employee stock options (ESOs) on bond yield spreads due to the revision of SFAS No. 123R (No.123R) which requires expensing ESO amounts. Using American bond observations from year 1995 to 2007, we find that the revision decreases the information benefits of ESOs disclosure. When controlling for credit ratings and potential endogeneity problems, we also find that ESOs are significantly and positively related to bond yield spreads in post-No.123R period while have an opposite effect in pre-No.123R period. We conclude that information effect mainly drives the ESO’s effects on credit risk in both pre- and post-No.123R periods.